Cost-effectiveness of an online supervised group physical and mental health rehabilitation programme for adults with post-COVID-19 condition after hospitalisation for COVID-19: the REGAIN RCT - Henry Nwankwo; James Mason; Martin Underwood; Julie Bruce; Ranjit Lall; Chen Ji; Mariam Ratna; Gordon McGregor (BMC, 2024)
Abstract Background Following the COVID-19 pandemic, millions of people continue to experience ongoing physical and mental health sequelae after recovery from acute infection. There is currently no specific treatment for the diverse symptoms associated with post-COVID-19 condition. Physical and mental health rehabilitation may help improve quality of life in such patients. This study reports the cost-effectiveness of a programme of physical and mental health rehabilitation compared to best practice usual care in people with post-COVID-19 condition who were previously hospitalised. Methods We conducted an economic evaluation within a randomised controlled trial from the perspective of the UK national health service (NHS) and personnel social services perspective (PSS). Resource used and health-related quality of life were collected using bespoke questionnaire and the EQ-5D-5 L questionnaire at three, six, and 12 months. Incremental costs and quality adjusted life years accrued over the follow-up period were estimated and reported as the incremental cost-effectiveness ratio. Estimate uncertainty was managed by multiple imputation and bootstrapping cost-effectiveness estimates; and displayed graphically on the cost-effectiveness plane. Results Over a 12-month time horizon, incremental costs and QALYs were £305 (95% CI: -123 to 732) and 0.026 (95% CI: -0.005 to 0.052) respectively. The ICER was £11,941 per QALY indicating cost-effective care. Sensitivity analyses supported the base case findings. The probability of the intervention being cost-effective at a £30,000 per QALY willingness-to-pay threshold was 84%. Conclusion The within-trial economic evaluation suggested that people with post-COVID-19 condition after hospitalisation should be offered a programme of physical and mental health rehabilitation as it likely reflects a cost-effective use of NHS resources. Hospitalisation for COVID-19 has become less commonplace: further evaluation in non-hospitalised patients may be worthwhile. Trial registration ISRCTN registry ISRCTN11466448 23rd November 2020.